PENGARUH ORIENTASI KEWIRAUSAHAAN DAN INOVASI PRODUK TERHADAP KINERJA USAHA KECIL MENENGAH DENGAN VARIABEL INTERVENING KEUNGGULAN BERSAING (STUDI PADA UKM DI BANJARMASIN) - Isra Ul Huda; Anthonius Karsudjono; Pupita Nia Maharani (Kresna Bina Insan Prima, 2020)
This study aims to determine and analyze the effect of Entrepreneurship Orientation and Product Innovation on the Performance of Small and Medium Enterprises with Intervening Competitive Advantage Variable. This study uses quantitative data analysis methods, the analysis technique is Partial Least Square (PLS). The reason for choosing to use the PLS method is the testing of the mediating role of an intervening variable. The results of the analysis conducted stated that the Entrepreneurship Orientation did not significantly influence Competitive Advantage and also the Performance of Small and Medium Enterprises. Product Innovation has a significant effect on Competitive Advantage and does not have a significant effect on the Performance of Small and Medium Enterprises and Competitive Advantage does not have a significant effect on the Performance of Small and Medium Enterprises. Entrepreneurship Orientation does not significantly influence Small Medium Enterprises Performance with Intervening Variable Competitive Advantage and Product Innovation has no significant effect on Small Medium Enterprises Performance with Intervening Competitive Advantage Variable